PENYUSUNAN ALAT UKUR STUDENT WELL-BEING UNTUK SISWA SEKOLAH MENENGAH - , riestya estika ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was designed to build a valid and reliable student well-being measurement of high school student. Preparation of the scale followed a series of steps including the selection of a basic theory for building the scale construct, formulation of aspects and behavioral indicators of the attribute, item writing, item review, content validation, field-testing, and validation by criteria. Data for the study was obtained from 1,550 students. Two versions of the scale were developed, namely the A-Format scale which is of narrative type and the B-Format scale which is of Likert type. The analysis showed that both versions of the scale had satisfactory reliability and validity. The use of the B-Format scale (Likert) is more recommended than A-Format scale (Narrative). Both of these scales were shown to be reliable research instruments which can potentially be used as screening instruments in school.